Respiratory Findings in Herd Dairy Farmworkers from the Nile Delta Region - Serya, Hend; El-Helaly, Mohamed; Mosbah EL-Diasty, Mohamed; Al-Wehedy, Adel; Elsherbeny , Enas (La Medicina del Lavoro, 2023)
Background: Dairy farmworkers are exposed to a variety of respiratory hazards, including organic and inorganic dust, allergens, disinfectants, and gases emitted by cows and their wastes resulting in a range of adverse health effects. In Egypt, large herd dairy farms (>1000 cattle) are growing in both size and number and thereby more workers are employed. However, there is a lack of studies on the respiratory health status of these workers. Accordingly, the present study aimed to determine the prevalence of respiratory problems, assess ventilatory functions, and highlight the predictors of abnormal spirometry patterns among Egyptian dairy farmworkers. Methods: A cross-sectional study was carried out on 282 male workers, of whom 141 were dairy farmworkers and the other 141, not involved in livestock handling, were enrolled as controls. Full history, clinical examination, and ventilatory function measurements were done for both groups. Results: Dairy farmworkers had a significantly higher prevalence of respiratory symptoms (throat irritation and/or sore throat, cough, sputum production, and difficulty breathing) than controls as well as bronchitis, wheezes on chest auscultation, and obstructive ventilatory patterns. Older age (>37 years), longer smoking duration (>10 years), and longer working duration (>4 years) were independent predictors of abnormal spirometry patterns, particularly obstructive patterns, in dairy farmworkers. Conclusions: Large herd dairy farms, despite being open and naturally ventilated, are hazardous to workers’ respiratory health. Hence, the provision of personal protective equipment, periodic spirometry examinations as well as mandatory breaks and days off, are highly urged.